Travel pictures authenticity in social media space - Zhou, Meng; Lu, Xiaoli; Wang, Bin (Annals of tourism research, 2023)
The existing research has paid limited attention to the authenticity of travel pictures in virtual space. Drawing on space production theory, this study explores the social construction process of landscape alienation of travel pictures, as well as authenticity negotiation and flow mechanisms. With the Red platform as an example, combining netnography and interviews with platform stakeholders, the study finds that landscape alienation is driven by various forces on social media that jointly manipulate bloggers' posting behavior to maximize commercial gains rather than share authentic experiences. The interactions between and evolution of landscape alienation, media cognition, and embodied experiences arising from the multi-subject game in social media space determine authenticity negotiation and flow. The theoretical and practical implications are also discussed. [Display omitted] •Travel pictures beautification is landscape alienation in virtual space production.•Space production theory can apply to the virtual tourism space.•Capital and bloggers dominate and manipulate social media authenticity negotiation.•Media cognition is the key to understanding travel pictures authenticity flow.•User-generated content may not originate from or reflect real tourism experiences.